2017
DOI: 10.1016/j.carbpol.2016.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-cellulose nanocrystal microencapsulation to improve encapsulation efficiency and stability of entrapped fruit anthocyanins

Abstract: For improving stability of fruit anthocyanins (ACN), this study investigated the use of cellulose nanocrystal (CNC) as a macroion crosslinking agent to develop blueberry anthocyanin extract (BB)-loaded chitosan (CH)-CNC microcapsules, and compared with CH-sodium tripolyphosphate (TPP) ones. The yield of microcapsules (∼6.9g) and total monomeric anthocyanin recovery (∼94%) were significantly (P<0.05) higher in CH-CNC microcapsules than those (∼0.3g and ∼33%, respectively) in CH-TPP microcapsules. ACN distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(44 citation statements)
references
References 29 publications
2
38
0
2
Order By: Relevance
“…That may be due to the formation of interconnection chain resulted from intermolecular chitosan-TPP bond. Similar trends were found on anthocyanin microcapsules prepared by chitosan-TPP ionic gelation technique [18], and heparin microcapsules produced by using emulsification-crosslinking technique [21].…”
Section: Morphology Of Anthocyanin Microcapsulessupporting
confidence: 74%
See 1 more Smart Citation
“…That may be due to the formation of interconnection chain resulted from intermolecular chitosan-TPP bond. Similar trends were found on anthocyanin microcapsules prepared by chitosan-TPP ionic gelation technique [18], and heparin microcapsules produced by using emulsification-crosslinking technique [21].…”
Section: Morphology Of Anthocyanin Microcapsulessupporting
confidence: 74%
“…Some others research agreed with the result. Anthocyanin encapsulation efficiency obtained by using ionic gelation technique with chitosan-NaTPP was 33% [18]. While, other research obtained anthocyanin encapsulation efficiency of 23% with similar technique, carrier material and cross-linker [19].…”
Section: Influence Of Stirring Intensity and Carrier Materials Concentmentioning
confidence: 85%
“…To date, many examples of CNCs in gels/foams/aerogels [329], microencapsulation [321,373], and emulsions (described above) have been reported. Envisioned food applications are similar to the already in-place use of cellulose derivatives and microcrystalline cellulose, where the CNC advantage is high specific surface area and their whisker shape.…”
Section: Upcoming Industrial Applications For Cncsmentioning
confidence: 99%
“…Nanofibers seemed to favor the release of the active compounds of clove essential oil probably due to the improved dispersion of clove essential oil in nanocomposites through a higher amount of smaller droplets . Recently, Wang et al demonstrated the superior benefits of using cellulose nanocrystals as the macro‐ion crosslinking agent in chitosan‐based microencapsulation for improving the encapsulation efficiency and stability of blueberry anthocyanin extracts, compared with the usage of chitosan‐sodium tripolyphosphate (TPP) microcapsules. cellulose nanocrystals incorporated chitosan functioned not only as a macro‐ion cross linking agent on the positively charged amino groups in chitosan, but also as fillers for chitosan matrix, thus generating more rigid and stable microcapsules.…”
Section: Introductionmentioning
confidence: 99%
“…cellulose nanocrystals incorporated chitosan functioned not only as a macro‐ion cross linking agent on the positively charged amino groups in chitosan, but also as fillers for chitosan matrix, thus generating more rigid and stable microcapsules. Chitosan‐cellulose nanocrystals microencapsulation could be extended to load other bioactive compounds and active food ingredients for various applications . Probiotic ( Lactobacillus rhamnosus ATCC 9595) was encapsulated in alginate‐cellulose nanocrystals‐lecithin microbeads to produce nutraceutical microcapsules.…”
Section: Introductionmentioning
confidence: 99%